Transarterial Chemoembolization (TACE) Combined with Sorafenib in Treatment of HBV Background Hepatocellular Carcinoma with Portal Vein Tumor Thrombus: A Propensity Score Matching Study. (28th July 2019) - Yuan, Jia; Yin, Xin; Tang, Bei; Ma, Hui; Zhang, Lan; Li, Lixin; Chen, Rongxin; Xie, Xiaoying; Ren, Zhenggang
Abstract : Objectives . Hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT) remains a challenge in management. Transarterial chemoembolization (TACE) has been used for patients with PVTT but efficiency was limited with a median overall survival of 4 to 6.1 months. The aim of this study is to evaluate the efficiency of TACE combined with sorafenib in HBV background HCC with PVTT. Methods . A total of 498 patients were enrolled in the study including 69 patients who received TACE combined with sorafenib and 429 patients treated with TACE alone between January 1st, 2008, and April 30st, 2014. Using the 1:2 propensity score matching, 138 well-balanced patients were enrolled. Overall survival (OS) was compared between the two groups. The Kaplan-Meier method was used to evaluate the OS, and the differences between groups were analyzed with a log-rank test. Results . TACE combined with sorafenib improved the OS of the patients compared with TACE alone (13.0 vs 6.0 months, p<0.001). After propensity score matching, the median OS of combination therapy and TACE were 13.0 and 7.0 months, respectively (p=0.001). Subgroup analysis revealed that the patients younger than 60 years old, male patients, AFP more than 400ng/ml, tumor size more than 5cm, or type III/IV PVTT had OS benefits from TACE combined with sorafenib. Conclusions . Compared with TACE therapy alone, TACE combined with sorafenib could improve OS in HBV background HCC patients with PVTT. The patients who are younger, male, or with more tumor burden may benefit more from combination therapy.